THE VERB POUVOIR IN FRENCH DIRECTIVES - Chinh, Nguyen Minh (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4605, 2020)
The article will analyse semantic and pragmatic characteristics of the verb pouvoir in French directive utterances, basing on the analysis of occurrences withdrawn from five different sub-corpora. This is to know how language skills are mobilized by French native speakers to satisfy the linguistic and social normative expectations in different situations. The study will use descriptive and statistical methods to clarify the grammatical and pragmatic characteristics of pouvoir as well as the trends of use in social situations in which speakers are involved.